A silicon rubber composite with enhanced thermal conductivity and mechanical properties based on nanodiamond and boron nitride fillers. Issue 9 (16th June 2021) - Qu, Jiaying; Fan, Lu; Mukerabigwi, Jean Felix; Liu, Cui; Cao, Yu
Abstract: Silicone rubber (SR) is a nonreactive and stable material that is widely applied in a wide variety of products including electrical and electronic appliances. Currently, the synthesis of SR with enhanced thermal conductivity and mechanical properties is of great significance. Herein, an improved thermal conductive SR composite was synthesized by using nanodiamond (ND) and boron nitride (BN) as composite thermal conductivity fillers to the terminal hydroxyl functional group of SR. We studied the thermal conductivity and mechanical properties of the composites as well as the effects of different ratios of BN and ND fillers on the properties of SR composite. The results show that the thermal conductivity of the SR composite filled with 6 phr ND and 70 phr BN was up to 0.82 W/m K, which was remarkably increased by 70.83% than that of modified by a single filler (i.e., 70 phr BN). Moreover, the SR composite prepared with dual fillers (BN‐ND) showed better thermal stability, and the maximum thermal degradation temperature that was higher than that of the composite prepared with a single filler and pure SR. Furthermore, the mechanical properties of the sample indicators were found to be better than those of the currently available similar products on the market. Abstract : In the silicone rubber modified by boron nitride (BN) and nanodiamond (ND) composite fillers, the larger BN particles and the smaller ND particles are staggered alternately, forming an effective thermal conduction path, which makes the sample have good thermal conductivity.